Alternative Insitutions on Dispute Settlement For Financial Services Sector (LAPS SJK) in Banking Disputes - Ningsih, Ayup Suran (Fiat Justisia: Jurnal Ilmu Hukum, 2023)
A dispute is a problem submitted by the Customer or Customer Representative to the bank mediation organizer, after going through the complaint resolution process by the Bank. When the customer feels that the problem is not resolved through Complaint to the Bank, a dispute is born here. Disputes between the Bank and the Customer are inevitable because of the legal relationship between the two. Dispute resolution solutions are carried out through litigation or court and non-litigation channels. One of the best steps in resolving disputes between banks and customers is through Mediation which is facilitated by the Alternative Insitutions on Dispute Settlement For Financial Services Sector/Lembaga Alternatif Penyelesaian Sengketa Sektor Jasa Keuangan (LAPS SJK). The purpose of writing this article is to examine the optimization of the role of mediation for banking disputes. The settlement process at LAPS for the Financial Services Sector is confidential. The term confidential here means that the announcement is not announced. It prioritizes a win-win solution. Therefore it is more comfortable for the parties. Ultimately there will also be able to maintain consumer confidence in the financial services sector.